Convergent Evolution of Locomotory Modes in Euarchontoglires - Geng, Wei-hang; Wang, Xiao-ping; Che, Li-feng; Wang, Xin; Liu, Rui; Zhou, Tong; Roos, Christian; Irwin, David M.; Yu, Li (Frontiers in Ecology and Evolution, 2020)
Abstract The research of phenotypic convergence is of increasing importance in adaptive evolution. Locomotory modes play important roles in the adaptive evolution of species in the Euarchontoglires, however, the investigation of convergent evolution of the locomotory modes across diverse Euarchontoglire orders is incomplete. We collected measurements of three phalangeal indices of manual digit III, including metacarpal of digit III (MC3), manus proximal phalanx of digit III (MPP3) and manus intermediate phalanx of digit III (MIP3), from 203 individuals of 122 Euarchontoglires species representing arboreal (orders Scandentia, Rodentia, and Primates), terrestrial (orders Scandentia and Rodentia) and gliding (orders Dermoptera and Rodentia) locomotory modes. This data can be separated into seven groups defined by order and locomotory mode. Based on combination of the three phalangeal indices, the Principle component analyses (PCA), phylomorphospace plot and C-metrics analyses clustered the arboreal species of Scandentia, Rodentia and Primates together and the terrestrial species of Scandentia and Rodentia together, and showed the convergent signal in evolution of the arboreal (C1=0.424, P<0.05) and terrestrial (C1=0.560, P<0.05) locomotory modes in Euarchontoglires. Although the gliding species from Dermoptera and Rodentia did not cluster together, they also showed the convergent signal (C1=0.563, P<0.05). Our work provides insight into the convergent evolution of locomotory modes in Euarchontoglires, and reveals that these three indices contribute valuable information for identifying convergent evolution in Euarchontoglires.